Smoking Hijabers Among Surabaya Teenagers from a Radical Feminist Perspective - Emylia, Najwa; Ridwan, Ahmad; Harianto, Sugeng; Listyani, Refti Handini (Jurnal Pendidikan Sosiologi dan Humaniora, 2026)
The phenomenon of teenage girls wearing hijabs who smoke in Surabaya shows tension between religious identity, society's moral demands, and social dynamics that shape teen behavior. The hijab, seen as a symbol of piety, often puts women's bodies under strict moral scrutiny, while at the same time teens face pressure to fit in with their friends and digital culture. This study aims to understand the motivations, identity meanings, and the possibility that smoking is seen as a form of resistance to patriarchal norms. Using a descriptive qualitative approach, data were obtained through in-depth interviews and non-participatory observations of hijab-wearing adolescents aged 14–18 years, supplemented by a literature review on the social construction of women and radical feminist theory. The results show that motivation for smoking is the need for social acceptance, which is influenced by FOMO, peer pressure, and digital culture. This is reinforced by the ideological motive that this behavior reflects adolescents’ efforts to negotiate their sense of self. However, in certain contexts, smoking also serves as a form of symbolic resistance against patriarchal control over women’s bodies. This study concludedes that the identity of women who wear the hijab is not singular. It is shaped through complex interactions between social structures, popular culture, and personal experiences. These findings open up space for further research on the representation of women who wear the hijab in digital culture and its implications for the negotiation of gender identity in urban Muslim communities.